The Implementation of Pancasila Principles on the Development of the Independent Curriculum in the Execution of the P5 Program: A Perspective from Educational Philosophy - Siti Nurislamiah; Ariesta Setyawati; Sherly Astuti (Didaktika: Jurnal Kependidikan, 2024)
Pancasila, as the nation's ideology, reflects the worldview of the Indonesian people. The relationship between Pancasila and education is outlined in Law No. 20 of 2003 on the National Education System. The Strengthening Pancasila Student Profile Project (P5) is a significant initiative in efforts to reinforce nationalist character in Indonesia. This study aims to explore the implementation of P5 through a literature review method, focusing on content analysis of various related literature. This research method involves gathering and analyzing data from policy documents, academic journals, books, research reports, and news articles. The results show that P5's implementation strategy includes developing an integrated curriculum, intensive teacher training, collaboration with local communities, and the use of educational technology. Despite challenges such as limited resources and integrating P5 into an already dense curriculum, there are recommendations to improve implementation, including strengthening teacher training, developing a more integrated curriculum, and applying continuous monitoring and evaluation. In conclusion, the implementation of P5 holds great potential in shaping the nationalist character and identity of Indonesian students, but comprehensive support from all stakeholders is needed to achieve long-term success.